Further comparison of isolated and synthesized contingencies in functional analyses. Issue 1 (19th November 2021) - Irwin Helvey, Casey; Van Camp, Carole M.
Abstract : Recent research on functional analyses (FAs) has examined the extent to which problem behavior is maintained by single (isolated) or combined (synthesized) reinforcement contingencies. Outcomes of these analyses might differ depending on the sources of information that are used to inform contingencies included in test conditions. The purpose of the current study was to compare the outcomes of isolated FAs and synthesized contingency analyses (SCAs) with 3 participants. Conditions in both analyses were informed by interviews and both unstructured and structured observations. Problem behavior for all 3 participants was maintained by 1 or 2 isolated reinforcers. Results suggested false‐positive SCA results for 2 participants. For 1 participant, a second isolated reinforcer was identified following the SCA, indicating the induction of a novel function. Implications for the use of isolated and synthesized consequences are discussed, as well as the predictive validity of the assessments that are used to inform them.